Developing a one-semester course in forensic chemical science for university undergraduates - Salem, Roberta Sue (Kansas State University, 2009)
The purpose of this study was to research, develop and validate a one-semester course for the general education of university undergraduates in forensic chemical education. The course outline was developed using the research and development (R&D) methodology recommended by Gall, Borg, and Gall, (2003) and Dick and Carey, (2001) through a three step developmental cycle. Information was gathered and analyzed through review of literature and proof of concept interviews, laying the foundation for the framework of the course outline. A preliminary course outline was developed after a needs assessment showed need for such a course. Professors expert in the area of forensic science participated in the first field test of the course. Their feedback was recorded, and the course was revised for a main field test. Potential users of the guide served as readers for the main field test and offered more feedback to improve the course.
Keywords: Forensics; Chemistry; Forensic chemistry; Forensic science; Forensics education; Undergraduate education; Chemistry, General (0485); Education, Adult and Continuing (0516); Education, Sciences (0714)